2021
DOI: 10.7600/jpfsm.10.263
|View full text |Cite
|
Sign up to set email alerts
|

Post-training urinary titin fragment concentration increases in athletes with previous muscle strain injury: a pilot study in soccer players

Abstract: Urinary titin fragment concentration has been established as a noninvasive biomarker of muscle protein degradation and muscle damage after exercise. We hypothesized that concerning the microdamage in the chronic phase of muscle strain injury, muscle damage is more likely to occur after exposure to training workload. We aimed to evaluate the urinary titin fragment concentration in professional soccer players who previously had muscle strain injuries (injured vs uninjured group: mean ± SEM age [years], 26.25 ± 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In competitive sports, athletes should be encouraged to focus on the task of identifying primary internal sensations of tiredness as RPE. In particular, previously injured players tend to damage micro-muscle fibers more compared to uninjured players, as mentioned before [43]. Such players tend to express higher sRPE depending on the condition of the injured area.…”
Section: Reconsider Internal Load Calculation For Previously Injured ...mentioning
confidence: 65%
See 1 more Smart Citation
“…In competitive sports, athletes should be encouraged to focus on the task of identifying primary internal sensations of tiredness as RPE. In particular, previously injured players tend to damage micro-muscle fibers more compared to uninjured players, as mentioned before [43]. Such players tend to express higher sRPE depending on the condition of the injured area.…”
Section: Reconsider Internal Load Calculation For Previously Injured ...mentioning
confidence: 65%
“…The study shows that larger urine titin fragment values are observed in previously injured football players after training compared to uninjured players [43].…”
Section: Increased Muscle Damagementioning
confidence: 69%